Phygital HR: Leveraging Digital Transformation For Organizational Resilience, Employee Well-Being, And Sustainable Work Cultures In Viksit Bharat (International Journal of Environmental Sciences, 2025)
The integration between physical and digital technologies - phygital HR – is revolutionizing organisational behavior (OB) and human resources management (HRM). As India moves towards Viksit Bharat 2047, digital HR tools like AI in recruitment, HR analytics and automation are re-imagining work design, wellbeing of employees and resilience of the organization. We focus on the effects of phygital HR practices on employee engagement, job satisfaction, and psychological well-being in hybrid workplaces by using socio-technical systems theory and Job Demands–Resources (JD -R) model.A mixed-method research design was followed and data were gathered through 450 employee-survey respondents across education-IT-service sectors in West Bengal, India, and 20 qualitative interviews. Structural equation modeling results show that organizational culture is a significant mediating mechanism between digital HR practices and the employee outcomes. These effects are furthermore moderated by demographic factors (age, gender, work type) with hybrid employees benefitting the most.The findings progress OB theory into the phygital era while offering organizations a road map to reconcile efficiency, inclusivity and well-being-in all, indispensable for creating sustainable work cultures consistent with India's Viksit Bharat vision.